Research on electric potentials alignment on the ground surface within the grounding conductor territory - I.V. Nizhevskyi (National Technical University "Kharkiv Polytechnic Institute", 2014)
Results of research on distribution of electric potentials on the earth surface in the territory with a grounding conductor are analyzed. It is shown that potential over the center of a square grounding conductor can be higher than that over the electrode. It is suggested to estimate the limit size of the cell of a complex net grounding conductor depending on the depth of its laying. It is found that a two-level design of the grounding conductor reduces touch voltage. Novelty of the results consists in application of a mathematical model to investigating electric characteristics of a two-level grounding conductor versus its laying depth.